The effect of different feeding regimes on enzyme activities of gut microbiota in Atlantic cod (Gadus morhua L.) - Askarian, Fatemeh; Sperstad, Sigmund; Merrifield, Daniel L; Arun Kumar, Ray; Ringø, Einar (Aquaculture Research, 2012)
The aims of this study were: (1) evaluate enzyme-producing bacteria isolated from the GI tract of Atlantic cod, (2) identify the most promising enzyme-producing bacteria by 16S rRNA gene sequencing and (3) to assess whether these bacteria have the ability to inhibit in vitro growth of four well known pathogenic bacteria; Aeromonas salmonicida subsp. salmonicida, V. (L.) anguillarum, Moritella viscosa and Carnobacterium maltaromaticum. In this study, 79 gut bacteria previously isolated from the GI tract of Atlantic cod fed fish meal (FM), soybean meal (SBM) and bioprocessed soybean meal (BPSBM) from the study of Ringø et al. (2006a), were randomly selected for further investigation. These bacteria had not previously been tested for enzyme-production, identified by 16S rRNA gene sequencing or tested for antagonistic activity. Determination of qualitative enzyme activities; protease, amylase, cellulase, phytase, lipase and chitinase were carried out as described by Ray, Roy, Mondal and Ringø (2010) and Askarian, Zhou, Olsen, Sperstad and Ringø (2011). These endogenous bacterial enzymes were selected as they might contribute to fish nutrition (Ray et al. 2011). Forty eight of the most promising enzyme-producing bacteria, 15, 16 and 17 isolated from the GI tract of Atlantic cod fed FM, SBM and BPSBM, respectively were further identified by 16S rRNA gene sequencing as described by Ringø, Sperstad, Myklebust, Mayhew and Olsen (2006b). All sequences were analysed and edited in BIOEDIT and blasted against the sequences available in GenBank. Gut bacteria showing low similarities (<94%) with known sequences in GenBank were treated as unknown.